Analisis Bakteri dalam Air Sungai Batanghari : Evaluasi Potensi Pencemaran Mikrobiologis dan Dampaknya terhadap Kesehatan Masyarakat di Jambi - Tamimil Hasanah; Ardi Mustakim (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
The Batanghari River is a vital water source in Jambi Province, used by the community for various purposes, including domestic, agricultural, and fisheries needs. However, with increasing human activities, such as the discharge of household waste, industrial waste, and agricultural waste, the river's water quality is at risk of microbiological contamination that can endanger public health and the environment. This study aims to identify the presence of bacteria in the Batanghari River water, in order to assess the potential for biological contamination that can negatively impact public health and the surrounding ecosystem. The method used in this study included taking water samples from several locations along the river. After sampling, bacterial isolation and identification were carried out using Nutrient Agar (NA) media using the pour method. The results of the isolation process showed the growth of bacterial colonies that varied in shape, size, and color, indicating microbiological contamination, especially by heterotrophic bacteria. These findings indicate that the Batanghari River water contains microorganisms that reflect the potential for microbiological contamination. Therefore, this study emphasizes the importance of regular water quality monitoring and the need for sustainable management measures to maintain the health of the ecosystem and surrounding community. With routine monitoring, it is hoped that potential contamination that could be harmful to health can be detected early. Furthermore, the results of this study are expected to form the basis for better policy-making in water resource management and increase public awareness of the importance of maintaining water quality for sustainable life and environmental health. This study provides a preliminary overview of the microbiological condition of the Batanghari River water and emphasizes the need for greater attention in water resource management to prevent negative impacts on health and the environment.